Resident's Attitudes Toward Tourism Development in Simanindo Subsdistrict Samosir Regency - Delita, Fitra; Berutu, Nurmala; Tanjung, Flores; Rambe, Tappil (KnE Social Sciences, 2024)
Tourism development especially in rural areas has changed residents’ economic, sociocultural, and environmental life. It’s important to analyze residents’ attitudes toward tourism development in their area. This study aimed to analyze the attitudes of the Batak Toba Ethnic as residents toward tourism development in Simanindo Subdistrict. This research was a quantitative study with a cross-sectional survey. A survey with 115 residents as representatives of Batak Ethnic was conducted in June 2022. The findings revealed that several challenges of tourism development had been stated by residents including conflict over resources ownership, less involvement of residents, inadequate financial support, insufficient facilities, low quality of service and product, poor marketing, and unskilled human resources. The Batak Toba Ethnic as residents also obtained positive and negative impacts of tourism development in their area. Positive impacts included conserving culture and heritage, preserving nature, supporting trading of local products, upgrading public facilities, encouraging economic growth, increasing employment opportunities, enhancing additional income, improving the quality of life, increasing foreign investors, improving the standard of living and personal benefit for residents. However, negative impacts were inconsiderable. The main suggestions toward tourism development were enhance local people involvement and participation, increase attractions, accessibilities and amenities. The economic benefits has high correlation toward communities involvement and participation in tourism development. Keywords: attitudes, challenges, impacts, participation, tourism development